Detecting the complex motion of self-propelled micromotors in microchannels by electrochemistry. Issue 102 (20th October 2016) - Khezri, Bahareh; Sheng Moo, James Guo; Song, Peng; Fisher, Adrian C.; Pumera, Martin
Abstract : Self-propelled micromotors were detected via impact electrochemistry technique in real time which allows the different modes of micromotor motions under channel environments to be recognized. Abstract : Autonomous self-propelled nano/micromotors are new frontiers in micro- and nanotechnology, with a plethora of possible applications in environmental remediation and biomedicine. However, key challenges remain, one of which is the monitoring of motion in these self-propelled nano- and microdevices. Tracking of these miniaturized objects is typically done by optical microscopy. Such a manual methodology has several inherent challenges, ranging from demanding computational power for optical image analysis to following objects in opaque or non-transparent environments. Here we developed a monitoring system for an autonomous self-propelled micromotor in a microfluidic channel via the placement of electrodes in the pathways. The electrochemical detection methodology, based on the disturbances in the electrical double layer of an electrode surface in our devised instrumentation technique, allows for different modes of motion in micromotors in channel environments to be recognized. This ability to detect the motion of autonomous self-powered micromotors in opaque/non-transparent channels will find widespread applications in the future.